P0782PROGNOSTIC IMPACT OF NECK CIRCUMFERENCE ON CARDIVASCULAR OUTCOMES AND MORTALITY IN PATIENTS WITH MODERATE CHRONIC KIDNEY DISEASE: AN ANALYSIS FROM THE GERMAN CHRONIC KIDNEY DISEASE (GCKD) STUDY. (6th June 2020) - Cejka, Vladimir; Störk, Stefan; Nadal, Jennifer; Schultheiß, Ulla T; Köttgen, Anna; Sommerer, Claudia; Sitter, Thomas; Meiselbach, Heike; Busch, Martin; Schneider, Markus; Saritas, Turgay; Kotsis, Fruzsina Kinga; et al.
Abstract: Background and Aims: Neck circumference (NC) is an approximator of upper body subcutaneous fat tissue and a marker of obesity. It has been shown to be associated with cardiovascular risk factors and incident chronic kidney disease (CKD). In CKD patients, the impact on cardiovascular events and all cause death has not been fully elucidated yet. The prognostic impact on these outcomes in a representative cohort of adult patients with moderate CKD of Caucasian origin was investigated here. Method: We used data from the GCKD study, a German multi-centric prospective observational cohort study of 5217 adults with moderate chronic kidney disease, defined as eGFR 30–60 mL/min/1.73 m2 or eGFR >60 mL/min/1.73 m2 and significant proteinuria (albuminuria >300 mg/g creatinine or proteinuria >500 mg/g creatinine). Exclusion criteria were active malignancy, heart failure NYHA class IV, organ transplantation, and non-Caucasian origin. NC was measured repeatedly (annually, except at first year of follow-up) during the study, therefore, the mean value was analyzed. We report data from the 4-year follow-up visit regarding 1) a combined endpoint of non-fatal myocardial infarction, non-fatal stroke, cardiovascular death, and peripheral artery disease event (amputation or revascularization) and 2) all-cause death as another endpoint. Cox proportional hazard regression was used to calculate hazard ratios (HR) with 95% CIs. In univariate analysis, ordinal regression with quintiles of NC was applied. Results: NC was accrued in 4453 participants and analyzed. NC overall was 40±5 cm (43±4 cm in men and 37±4 cm in women, p<0.001), mean age 60±12 years, 41% were female, 96% had hypertension, 35% were diabetic, 58% had ever smoked, eGFR was 50±18 ml/min/1.73 m (CKD-EPI), BMI 28±6 kg/m, LDL-cholesterol 119±43 mg/dl. Higher quintiles of NC were associated increased risk of the cardiovascular outcome in univariate analysis: highest (44 cm) vs. lowest (36.5 cm), HR 2.34 (1.63–3.36; p<0.001). In multivariable analysis adjusted for age, sex, and BMI, this effect was reduced but still apparent: HR 1.04 (1.01–1.08, p=0.025). Age (HR per year 1.05, 1.04–1.07, p<0.001), and female sex (HR 0.69, 0.50–0.95, p=0.023), showed also significant effects, whereas BMI did not (p=0.831). The effect of higher quintiles of NC on the risk of all-cause death in univariate analysis was even stronger: highest vs. lowest, HR 3.2 (1.72–5.81, p=0.006). However, after adjustment this effect was abolished: HR 0.99 (0.95–1.04; p=0.85). Only age (HR 1.07, 1.04–1.09, p<0.001), and female sex (HR 0.45, 0.27-0.74, p=0.002), remained significant predictors of all-cause death in this model. Conclusion: In patients with chronic kidney disease, we found higher NC to be associated with increased cardiovascular event risk, but not all-cause death, after adjustment for age, sex and BMI. The risk of cardiovascular outcomes and overall mortality was consistently lower in women. Our analysis supports evidence, that upper body subcutaneous adipose tissue might be an independent contributor to cardiovascular event risk.